Analysis of The Influence of Agro-Tourism on The Socio-Economy of The Community in Islamic Perception - Fira Nafisah; Yusrizal; Aqwa Naser Daulay (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
The purpose of this study is to provide knowledge and analyze the significant influence of agro-tourism development on socio-economic improvement. The method used in the study is a quantitative method with simple regression analysis, the data used is secondary data by providing questionnaires and distributed to residents and workers in Pematang Johar Rice Field Tourism. The number of samples used was as many as 50 respondents, in sampling it was determined by the criteria of workers and residents of the area around the Pematang Johar tour. The results obtained are that agro-tourism variables have a significant effect on the socio-economy in Pematang Johar Deli Serdang rice field tourism, which is in line with According to Zaqiah Ramdani and Tuti Karyani who said that agro-tourism has an effect on the socio-economy, this is evidenced by their research which says that the agro-tourism created makes people's income increase, the absorption of labor is increasing, and household needs are met. This explains with this research that agrotourism was created to strengthen and improve the economy of the surrounding community such as creating jobs, utilizing agriculture as tourism and continuing to produce and carry out farming activities, so that the benefits obtained by the surrounding community increase.